Pilomatrix carcinoma of the vulva - Mihae Song; Marina Chekmareva; Gloria Bachmann; Darlene Gibbon (Elsevier, 2016)
Background: Pilomatrix carcinomas are rare, frequently occurring in older male patients. We report a case of vulvar pilomatrix carcinoma in a 30-year-old woman, the second known reported case occurring on the external genitalia. Case: A 30-year-old female originally presented at an outside institution for the management of an asymptomatic vulvar mass that was biopsied and read as invasive squamous cell carcinoma. Pathology review at our institution reclassified the vulvar mass as a low-grade pilomatrix carcinoma. The patient underwent radical hemivulvectomy without an inguinal-femoral groin node dissection. She has remained without evidence of disease recurrence for more than 5 years since her diagnosis. Conclusion: Pilomatrix carcinoma can be confused for an invasive squamous cell carcinoma. Due to its low risk of metastases, a less radical surgical approach can be taken. Consideration of this unusual malignancy is important in the determination of appropriate management.